Sympathy or distress? The moderating role of negative emotion differentiation in helping behavior - Jeong, Sophia Soyoung; Gong, Yuanyuan; Henderson, Alexandra (Asia Pacific journal of management, 2023)
Past research has documented the many psychological and behavioral benefits of negative emotion differentiation, that is, the degree to which one can identify, distinguish, and describe specific negative feeling states. Drawing on Affective Events Theory, we argue that negative emotion differentiation affects how individuals react to a need-laden affective event (i.e., being in a situation where one is asked for some assistance). Specifically, we posit that individuals high in negative emotion differentiation will be more adept at interpreting their negative emotions as arising from others' needs (i.e., moral emotions) and regulating them through helping behavior. We tested this basic premise in two studies conducted in East Asia – a field study involving working adults in a general work setting and a quasi-experiment involving a student sample. In both studies, we examined the role of negative emotion differentiation in how individuals respond to negative emotions facing a need-laden affective event. The results supported our predictions, as high negative emotion differentiation weakened the negative relationship between general negative emotions and subsequent helping behavior (Study 1) and strengthened the positive relationship between negative moral emotions and helping behavior (Study 2). Theoretical and practical implications are discussed.